Spoon Test for Puréed Food - Wendy J. Dahl; Jamila R. Lepore (EDIS)
Puréed foods prepared for people with swallowing problems should meet the recommended textural guidelines. Proper texture is the priority when creating purées. A puréed food should have a uniform texture that is “spoon thick” and does not require chewing. It should not be too dry, sticky, lumpy, or thin. Adjustments in thickness may be made according to the individual’s specific needs. This 2-page fact sheet was written by Wendy J. Dahl and Jamila R. (Frazier) Lepore, and published by the UF Department of Food Science and Human Nutrition, November 2012.